Morphological and molecular characterization of two trematode worms in the gastropod Asolene pulchella (Anton, 1859) - Dellagnola, F. A. (2017)
Asolene pulchella (Anton, 1859) Asolene pulchella (Caenogastropoda, Ampullariidae) is a native gastropod from La Plata River. In a previous study we reported the presence of parasite forms of Trematoda (Plathyhelminthes) in the digestive gland of adult snails from Regatas Lake (Buenos Aires). In this work identified two parasites with a morphological and molecular approach. The digestive gland of A. pulchella showed a large amount of larval forms (sporocysts and rediae) with internal cercariae in diverse degree of development.